The Effect of Local Taxes, Special Allocation Funds, and Budget Surplus on Capital Expenditure in Regencies and Cities of South Sulawesi Province - Puti Lia Maharani; Sri Hartaty; Maulidia Berlianti (LifeSciFi, 2026)
Regional fiscal capacity plays a crucial role in infrastructure investment. This study examined the effect of local taxes, special allocation fund, and budget surplus on capital expenditure in regencies and municipalities in South Sulawesi Province. The research employed a quantitative approach using secondary data obtained from the budget realization reports of 24 local governments during the 2020–2024 period, collected from the audit board of the Republic of Indonesia. Since the population consisted of all regency and municipal governments, a saturated sampling technique was applied, allowing the entire population to serve as the research sample. Panel data regression analysis was conducted using EViews version 13. The findings revealed that local taxes, special allocation fund, and budget surplus each had a positive and statistically significant effect on capital expenditure. Furthermore, the simultaneous test confirmed that the three independent variables jointly exerted a significant influence on capital expenditure across regencies and municipalities in South Sulawesi Province. The findings imply that local governments should strengthen local tax collection, optimize the utilization of special allocation funds, and manage budget surpluses more effectively to increase capital expenditure, improve public infrastructure, enhance service quality, and promote sustainable regional economic development.